(untitled) (Journal of Enam Medical College, 2018)
Background: Thalassaemia is one of the most common hereditary diseases worldwide including Bangladesh. Multitransfused thalassaemia patients may acquire hepatitis C virus infection in spite of currently practicing screening schedule. It is postulated that there are some pitfalls in the currently practicing screening system behind the transmission of HCV in transfusion-dependent thalassaemia patients. Objectives: To find out the prevalence of hepatitis C virus infection in transfusiondependent thalassaemia patients and thereby to see the efficacy of currently practicing screening schedule for hepatitis C virus. Materials and Methods: This cross-sectional study was conducted from 1st December, 2015 to 30th November, 2016 at Dhaka Shishu (Children) Hospital Thalassemia Center (DSHTC). Three hundred and twenty patients of multitransfused β-thalassaemia major and Hb E β-thalassaemia aged 3−18 years were enrolled. History was taken and physical examination was done. Blood specimens were collected and sent to the standard laboratory for detection of antibody against hepatits C virus. Results: Among the subjects, 174 (54.3%) were male and 146 (45.7%) were female. Out of total 320 patients, 75 (23%) were β-thalassaemia major and 245 (77%) were Hb E β-thalassaemia. Among the 320 thalassaemia cases, 47 were found positive for anti-HCV with an overall prevalence of 14.7%. Conclusion: Despite screening of blood donors by Rapid Device (Strip) Method, HCV infection remains an important cause of viral hepatitis infection among multitransfused thalassaemia children. J Enam Med Col 2018; 8(1): 16-19